Studi Perencanaan Perkerasan Lentur pada Peningkatan Ruas Jalan Condong-Wangkal Sta. 0+000 - Sta. 7+350 - Oktaviadi, Reza; Cahyono, Andri Dwi; Pratikto, Herlan (Jurnal Talenta Sipil, 2025)
Improving the quality of road sections is essential to address frequently occurring damage, such as surface cracks, potholes, and elevation reductions caused by pavement age exceeding the technical design limits. This condition directly impacts community productivity due to longer travel times, hampered distribution of goods and services, and disrupted inter-regional accessibility. Consequently, this reduces community mobility and slows regional economic growth. Probolinggo Regency, located in the northern coastal part of East Java Province, is one of the areas facing these problems. This study aims to accurately design a flexible pavement structure and prepare a cost budget plan (RAB) based on the 2024 Road Pavement Design Manual (MDPJ) guidelines. The research methods used include an average daily traffic volume (LHR) survey, subgrade quality testing, and pavement layer thickness calculations based on technical parameters. The planning results indicate that the pavement structure consists of a 6 cm thick Laston AC-WC wearing layer, a 20 cm thick class A aggregate base layer, and a 15 cm thick class B aggregate base layer. This thickness is considered sufficiently efficient in withstanding existing traffic loads. The estimated cost of implementing the road improvements is estimated at Rp616,433,000.00. The results of this study are expected to provide an efficient and sustainable technical solution to support smooth transportation, improve inter-regional connectivity, and stimulate economic growth in Probolinggo Regency.